Evolutionary increase in genome size drives changes in cell biology and organ structure - Itgen, Michael Walter, author; Mueller, Rachel Lockridge, advisor; Sloan, Daniel B., committee member; Hoke, Kim L., committee member; Zhou, Wen, committee member (Colorado State University. Libraries, 2022)
The evolution of large genome size has been associated with patterns of phenotypic change in cell and organismal biology. The most fundamental of these is between genome size and cell size, which share a strong positive and deterministic relationship. As a result, increases in cell size alter the structure and function of the cell. Genome and cell size, together, are hypothesized to produce emergent consequences on development and physiology at the cellular and organismal level. My dissertation aims to better understand these patterns and identify potential mechanisms underlying these phenotypic changes. I test for the effects of genome and cell size on cell function, cellular physiology, and organ morphology by leveraging the natural variation in genome size found in salamanders (Genus: Plethodon). First, I show that transcriptomic data supports the predictions that large genome and cell size has functional consequences on cell biology. I also reject the hypothesis that large cell size is functionally linked to lower metabolic rate at the cellular level, but I provide transcriptomic evidence that cell size alters the metabolic state of cells. Finally, I show that genome and cell size drives morphological change in organ-specific ways in the heart and liver. I conclude that large cell size does not lower metabolic rate in salamanders. As an alternative, I propose that the evolution of low metabolic rate lifts the constraint of cell size, thus permitting the evolution of genome gigantism.
Keywords: genome size; physiology; cell biology; salamanders; morphology